Implementasi Penegakan Hukum Undang-Undang Nomor 18 Tahun 2014 terhadap Perlindungan Hukum dan Kendalanya pada Orang dengan Gangguan Jiwa di Kota Semarang - Annisa Auwla Fil Ibadiyah; Dyah Listyarini; Arikha Saputra (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The number of people with mental disorders in Semarang City continues to increase. The large number of people with mental disorders in Semarang needs to be addressed seriously to prevent causing discomfort in social activities. Therefore, the author compiled a journal titled